The Digital Battlefield: Investigating the Role of Online Platforms and Social Media in Shaping the Chana Movement’s Quest for Democracy and Justice - Yuhannan, Abdullah (Journal of Roi Kaensarn Academi, 2024)
The Chana Community Movement in Thailand’s Songkhla province opposes a government industrial estate project that threatens the region's environmental and cultural heritage. This study explores how the movement leverages online platforms to mobilize support, organize protests, and communicate its message, while also addressing the challenges posed by digital tools. Using a qualitative case study approach, data were gathered from primary and secondary sources, including observations and stakeholder interviews, and analyzed thematically. The findings reveal that while digital platforms are essential for communication and mobilization, they also introduce significant challenges, such as misinformation, government surveillance, and the digital divide, which can hinder inclusive participation. The movement's success depends on effectively integrating digital tools with offline activism and addressing the risks associated with online manipulation. This study contributes to the broader discourse on digital activism by illustrating how online platforms can both empower and complicate social movements in the digital age.